ANALISIS KESALAHAN INTONASI DAROU PADA MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG ANGKATAN 2018 FKIP UNIVERSITAS RIAU - Muhammad Nasirudin; Arza Aibonotika; Adisthi Martha Yohani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: An Intonation is one of the most important element that affect the meaning of some sentence. Specifically Darou Intonation, which is the meaning of the word will changed if the intonation is wrong. The goal of this study is to find how a miss pronunciation on intonation of darou. this study is using a descriptive qualitative method. also instrument that used on this study is using speaking test. The respondent that participate on this study are 34 people's from 2018 class of japanese language education study program Riau University. Final result of this study indicating that half of student that participating on speaking test still wrong on the test.Key Words: Darou, Error, Intonation